Assessing motivations for non‐living and living organ donation among individuals with and without a history of blood donation. Issue 2 (15th February 2022) - France, Christopher R.; France, Janis L.; Ysidron, Dominic W.; Samstein, Benjamin
Abstract: Objectives: The current study investigated relationships between a history of blood donation, registration as a non‐living and living organ donor, and differential motivations. Background: Motivational commonalities exist between blood and organ donors, but there is no prior data on the relationships between blood donation history and both living and non‐living organ donor registration and motivation. Methods/materials: Participants completed online surveys assessing blood donation history, organ donor registration and interest, and motivations related to donation behaviour. Results: Blood donation history was not significantly related to registration as either a non‐living organ donor (blood donors = 81.4%; non‐blood donors = 76.4%) or as a living organ donor (blood donors = 14.0%; non‐blood donors = 10.9%). Further, blood donation history was not related to interest in learning more about being an organ donor. Compared to those not registered as an organ donor, those who were registered reported more positive organ donation motivations, but these relationships were unrelated to prior blood donation history. Conclusion: The present findings are consistent with existing research on attitudes, warm glow, and identity as organ donation motivators, and provide novel information regarding the importance of independent assessment of motivations for non‐living and living organ donation.